(untitled) (CIPEEX, 2022)
WITH THE BEGINNING OF A SIMPLIFIED WRITTINGFROM THE SUMERIAN PEOPLE, AROUND3.500 B.C. HUMANKIND STARTED BEING ABLE TO STORAGE AND REGISTER ITS OWN LAWS, CULTUREAND HISTORY IN CLAY BRICKS AND AFTERWARDS, SCROOLS.WITH THE ARRIVAL OF THE TECHNICALSCIENTIFIC-INFORMATIONAL REVOLUTION, AROUND THE XX CENTURY, THE WAY INFORMATION WASKEPT CHANGED, SWITCHING FROM PHYSICAL RECODS TO DIGITAL ONES.THIS WORK HAS THEOBJECTIVE OF DEVELOPING A PLATFORM UNTIL THE END OF THE COURSE, HAVING THE FUNCTIONALITYOF HELPING INSTITUTIONAL MANAGEMENT, BEING PUBLIC OR PRIVATES. IT IS WORTH TO POINT THATTHE MANAGEMENT OF EDUCATIONAL ORGANIZATIONS WILL HAPPEN THROUGH MODULES FOR THATESPECIFIC REA, FOR EXAMPLE, MODULES FOR SIGNING UP, RELEASE/ANALYSIS OF SCORES ANDFREQUENCY, RESERVING/ ANALYSIS OF PHYSICAL SPACES, EVENT CONTROLS, AND OTHERS. THEPRIORITY FOR PROJECT PROTOTYPE DEVELOPMENT WILL UTILIZE A FEW TECHNOLOGIES, FOR EXAMPLE,JAVASCRIPT AND DJANGO LIBRARIES ASIDE FROM PYTHON FRAMEWORK. HAVING OBJECTORIENTATION AS PROGRAMMING AND DATA BANK PARADIGMS. AS RESULTS, IT IS EXPECTED APLATFORM THAT IS INTUITIVE, RESPONSIVE, ESTABLE AND SECURE.